A TiO2 / GO@PLL bone-inducing composite material and its preparation method
Patent Information
- Application Number
- CN202410197755.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-22
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-02-22
AI Technical Summary
[0004]为了解决二氧化钛在可见光下的抗菌性能降低的问题以及PLL与二氧化钛之间存在结合困难等问题,本发明的目的在于提供一种双光热强效抗菌的TiO2/GO@PLL骨诱导复合材料的制备方法
[0021] 1. This invention modifies the surface of titanium dioxide with graphene oxide via electrostatic interaction to prepare a TiO2/GO composite material. Then, through the free combination of the carboxyl groups of graphene oxide and the amino groups of lysine, an amide bond is formed, which has strong adhesion and promotes cell proliferation and adhesion, further enhancing the osteoinductive ability of the photoresponsive material. Thus, a potent bactericidal TiO2/GO@PLL osteoinductive composite material with dual photoresponsiveness is constructed, which has excellent biomimetic properties of natural hard tissue and is expected to provide a basis for the preparation of novel inorganic/organic biomedical materials with excellent comprehensive performance, potent antibacterial and osteogenic properties.
Smart Images

Figure CN118059300B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical materials technology, specifically to a TiO2 / GO@PLL bone-inducing composite material and its preparation method. Background Technology
[0002] In recent years, titanium and titanium alloy implants have been widely used in bone repair fields such as orthopedics and dentistry due to their good biocompatibility, chemical stability, and mechanical properties. Current research on optimizing bone implants mainly focuses on surface modification to promote cell differentiation, induce bone regeneration, and enhance antibacterial capabilities. Titanium dioxide, as a photocatalytic material, can generate reactive oxygen species (ROS) under ultraviolet light irradiation to kill bacteria. However, the recombination of photogenerated electrons and holes generated under light reduces the photocatalytic and antibacterial properties of titanium dioxide, limiting its actual antibacterial effect. Therefore, an ideal titanium implant should possess controllable antibacterial surface properties based on stable long-term tissue regeneration guidance characteristics. Thus, surface modification is often used to improve the antibacterial properties of titanium dioxide under visible light.
[0003] Furthermore, while titanium dioxide possesses good biocompatibility, its lack of bioactivity and low mechanical strength limit its clinical application under certain load-bearing conditions. Polylysine (PLL) is commonly used as a molecular loading carrier, binding with biomolecules such as DNA, proteins, viruses, and bacteria on or within nanoparticles to enhance bioactivity. Therefore, the inventors attempted to incorporate PLL into titanium dioxide to promote cell growth and differentiation, and improve cell viability and metabolic activity. However, during the research process, they discovered difficulties in the binding of PLL to titanium dioxide. Based on this, the present invention aims to propose a PLL-modified titanium dioxide composite material that can inhibit bacterial infection while promoting bone healing. Summary of the Invention
[0004] To address the issues of reduced antibacterial properties of titanium dioxide under visible light and difficulties in bonding PLL with titanium dioxide, this invention aims to provide a method for preparing a TiO2 / GO@PLL bone-inducing composite material with dual photothermal strong antibacterial properties.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] The first aspect of the present invention provides a method for preparing a TiO2 / GO@PLL bone-inducing composite material, comprising the following steps:
[0007] Titanium dioxide dispersion and GO dispersion were ultrasonically mixed, and after removing the solvent, they were calcined at 300-350℃ to obtain TiO2 / GO composite material.
[0008] The TiO2 / GO composite material was immersed in a polylysine solution to modify the surface of the TiO2 / GO composite material with polylysine, thus obtaining the TiO2 / GO@PLL bone-inducing composite material.
[0009] In some preferred embodiments, the mass ratio of titanium dioxide to GO is 200:8 to 10.
[0010] In some preferred embodiments, the concentration of the polylysine solution is 0.8–1 g / L.
[0011] In some preferred embodiments, the pH of the titanium dioxide dispersion is 3 to 5.
[0012] In some preferred embodiments, the titanium dioxide dispersion is prepared as follows:
[0013] Titanium dioxide nanoparticles were dispersed in water at a pH of 3–5 to obtain a titanium dioxide dispersion.
[0014] In some preferred embodiments, the GO dispersion is prepared as follows:
[0015] GO was dispersed in an ethanol solution to obtain a GO dispersion.
[0016] In some preferred embodiments, the volume percentage of the ethanol solution is 60-90%.
[0017] In some preferred embodiments, the calcination time is 1 to 3 hours.
[0018] In some preferred embodiments, the soaking time is 20 to 60 minutes.
[0019] A second aspect of the present invention provides a TiO2 / GO@PLL bone-inducing composite material, which is prepared by the preparation method described in the first aspect.
[0020] The beneficial effects of this invention are:
[0021] 1. This invention modifies the surface of titanium dioxide with graphene oxide via electrostatic interaction to prepare a TiO2 / GO composite material. Then, through the free combination of the carboxyl groups of graphene oxide and the amino groups of lysine, an amide bond is formed, which has strong adhesion and promotes cell proliferation and adhesion, further enhancing the osteoinductive ability of the photoresponsive material. Thus, a potent bactericidal TiO2 / GO@PLL osteoinductive composite material with dual photoresponsiveness is constructed, which has excellent biomimetic properties of natural hard tissue and is expected to provide a basis for the preparation of novel inorganic / organic biomedical materials with excellent comprehensive performance, potent antibacterial and osteogenic properties.
[0022] 2. The TiO2 / GO@PLL bone-inducing composite material with dual light response constructed in this invention helps to improve the bioactivity and mechanical properties of the material without changing the properties of the substrate itself, thereby achieving the purpose of strong bactericidal effect. Attached Figure Description
[0023] Figure 1 The image shows the SEM images of the TiO2 / GO@PLL bone-inducing composite material and TiO2 prepared in Example 1 of this invention.
[0024] Figure 2 This is a graph showing the antibacterial data of the TiO2 / GO@PLL bone-inducing composite material prepared in Example 1 of the present invention. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0026] Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0027] Titanium dioxide, as a photocatalytic material, can generate reactive oxygen species (ROS) to kill bacteria under ultraviolet light irradiation. However, the recombination of photogenerated electrons and holes under light reduces the photocatalytic and antibacterial properties of titanium dioxide, limiting its actual antibacterial effect. Therefore, an ideal titanium implant should possess controllable antibacterial surface properties based on stable long-term tissue regeneration guidance characteristics. Thus, surface modification is often used to improve the antibacterial properties of titanium dioxide under visible light.
[0028] Furthermore, while titanium dioxide possesses good biocompatibility, its lack of bioactivity and low mechanical strength limit its clinical application under certain load-bearing conditions. Polylysine (PLL) is commonly used as a molecular loading carrier, binding with biomolecules such as DNA, proteins, viruses, and bacteria on or within nanoparticles to enhance bioactivity. Therefore, the inventors attempted to incorporate PLL into titanium dioxide to promote cell growth and differentiation, and improve cell viability and metabolic activity. However, during the research process, they discovered difficulties in the binding of PLL to titanium dioxide. Based on this, the present invention aims to propose a PLL-modified titanium dioxide composite material that can inhibit bacterial infection while promoting bone healing.
[0029] Graphene oxide, or GO, possesses excellent mechanical, optical, tribological, thermal, and electronic properties. GO is characterized by its unique sp and sp... 2Hybridized carbon atoms endow the material with a unique electronic structure and superior conductivity, which is highly conducive to electron transfer and enhances the catalytic activity of metals and their oxides. Furthermore, GO exhibits excellent stability and biocompatibility, demonstrating good antibacterial activity by generating ROS (reactive oxygen species) that directly contact the material surface under visible light. In addition, GO possesses good osteogenic capacity and the ability to promote cell proliferation and differentiation. Therefore, GO is an ideal material for coordinating the dual functions of titanium dioxide implants.
[0030] This invention presents a method for preparing a self-assembled TiO2 / GO@PLL osteoinductive composite material. During the self-assembly process, non-covalent interactions endow the resulting inorganic and organic structures with unique properties. The method involves electrostatically modifying the surface of titanium dioxide with graphene oxide to prepare the TiO2 / GO composite material. Then, amide bonds are formed through the free combination of the carboxyl groups of graphene oxide and the amino groups of lysine, exhibiting strong adhesive forces that promote cell proliferation and adhesion, further enhancing the osteoinductive ability of the photoresponsive material. This results in a potent antibacterial TiO2 / GO@PLL osteoinductive composite material with dual photoresponsiveness, possessing excellent biomimetic properties of natural hard tissue. This material holds promise for providing a basis for the preparation of novel, potent, antibacterial, and osteogenic biomedical materials with superior comprehensive properties.
[0031] The first aspect of the present invention provides a method for preparing a TiO2 / GO@PLL bone-inducing composite material, comprising the following steps:
[0032] Titanium dioxide dispersion and GO dispersion were ultrasonically mixed, and after removing the solvent, they were calcined at 300-350℃ to obtain TiO2 / GO composite material.
[0033] The TiO2 / GO composite material was immersed in a polylysine solution to modify the surface of the TiO2 / GO composite material with polylysine, thus obtaining the TiO2 / GO@PLL bone-inducing composite material.
[0034] In some preferred embodiments, the mass ratio of titanium dioxide to GO is 200:8 to 10. Examples include 200:8, 200:9, and 200:10.
[0035] In some preferred embodiments, the concentration of the polylysine solution is 0.8–1 g / L. Examples include 0.8 g / L, 0.9 g / L, and 1 g / L.
[0036] In some preferred embodiments, the pH of the titanium dioxide dispersion is 3–5. Examples include pH=3, pH=3.5, pH=4, pH=4.5, and pH=5. When the pH value is low, titanium dioxide-OH groups form on the surface of the nano-TiO2. 2+ This results in the particle surface carrying a positive charge.
[0037] In some preferred embodiments, the titanium dioxide dispersion is prepared as follows:
[0038] Titanium dioxide nanoparticles were dispersed in water at a pH of 3–5 to obtain a titanium dioxide dispersion.
[0039] In some preferred embodiments, the GO dispersion is prepared as follows:
[0040] GO was dispersed in an ethanol solution to obtain a GO dispersion.
[0041] In some preferred embodiments, the volume percentage of the ethanol solution is 60-90%. Examples include 60%, 65%, 70%, 75%, 80%, 85%, and 90%. Of course, the present invention does not limit the specific concentration of the ethanol solution; under other suitable circumstances, the concentration of the ethanol solution can be adjusted to match specific dispersion conditions.
[0042] In some preferred embodiments, the calcination time is 1 to 3 hours. For example, 1 hour, 2 hours, 3 hours, etc.
[0043] In some preferred embodiments, the soaking time is 20–60 minutes. Examples include 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, and 60 minutes. This invention does not limit the specific soaking time; the soaking time can be adjusted as needed.
[0044] A second aspect of the present invention provides a TiO2 / GO@PLL bone-inducing composite material, which is prepared by the preparation method described in the first aspect.
[0045] This invention uses TiO2, GO, and PLL as raw materials and employs self-assembly technology to obtain a photothermal antibacterial composite coating with uniformly dispersed titanium dioxide nanoparticles. The antibacterial composite coating of this invention enables the uniform distribution of titanium dioxide nanoparticles and enhances the mechanical properties and bioactivity of the material.
[0046] This invention constructs a potent bactericidal TiO2 / GO@PLL bone-inducing composite material with dual photoresponse. Without altering the properties of the substrate itself, it helps to improve the bioactivity and mechanical properties of the material, thereby achieving the purpose of potent bactericidal action.
[0047] The osteoinductive composite material of this invention can rapidly and effectively kill bacteria by generating local high temperature and reactive oxygen species under near-infrared radiation. It has the effects of rapid antibacterial action and promoting bone repair. The operation process is simple and solves the problems of bacterial infection caused by bone defects and transplantation surgery, thereby promoting bone healing. It is a photothermal antibacterial material with the potential to cure bone defects. Specific Implementation
[0049] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.
[0050] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0051] Unless otherwise specified, the methods described in the following embodiments are conventional methods; the reagents and materials mentioned are commercially available unless otherwise specified.
[0052] In the following embodiments, GO is graphite oxide; PLL is polylysine.
[0053] Example 1
[0054] A method for preparing a TiO2 / GO@PLL bone-inducing composite material includes the following steps:
[0055] (1) Preparation of TiO2 / GO composite material
[0056] 200 mg of titanium dioxide nanoparticles were dispersed in water at pH 4 and magnetically stirred for 1 hour at room temperature to obtain a titanium dioxide dispersion.
[0057] Mix 30 mL of water and 60 mL of ethanol thoroughly to prepare an ethanol-water mixed solution; disperse 10 mg of GO in the ethanol-water mixed solution to obtain a GO dispersion;
[0058] After mixing the GO dispersion and the titanium dioxide dispersion, the mixture was sonicated for 2 hours, then the solvent was removed, and the resulting composite material was calcined in a muffle furnace at 350°C for 2 hours to obtain the TiO2 / GO composite material.
[0059] (2) Preparation of TiO2 / GO@PLL bone-inducing composite material
[0060] The TiO2 / GO composite material was immersed in a 1 g / L PLL solution for 30 min, filtered, and then dried in a conventional drying oven at 60 °C for 2 h until completely dried to obtain the TiO2 / GO@PLL bone-inducing composite material.
[0061] Example 2
[0062] A method for preparing a TiO2 / GO@PLL bone-inducing composite material includes the following steps:
[0063] (1) Preparation of TiO2 / GO composite material
[0064] 200 mg of titanium dioxide nanoparticles were dispersed in water at pH 3 and magnetically stirred for 1 hour at room temperature to obtain a titanium dioxide dispersion.
[0065] Mix 30 mL of water and 60 mL of ethanol thoroughly to prepare an ethanol-water mixed solution; disperse 8 mg of GO in the ethanol-water mixed solution to obtain a GO dispersion;
[0066] After mixing the GO dispersion and the titanium dioxide dispersion, the mixture was sonicated for 2 hours, then the solvent was removed, and the resulting composite material was calcined in a muffle furnace at 330℃ for 2 hours to obtain the TiO2 / GO composite material.
[0067] (2) Preparation of TiO2 / GO@PLL bone-inducing composite material
[0068] The TiO2 / GO composite material was immersed in a PLL solution with a concentration of 0.9 g / L for 40 min. After filtration, it was dried in a normal drying oven at 60 °C for 2 h until completely dried, thus obtaining the TiO2 / GO@PLL bone-inducing composite material.
[0069] Example 3
[0070] A method for preparing a TiO2 / GO@PLL bone-inducing composite material includes the following steps:
[0071] (1) Preparation of TiO2 / GO composite material
[0072] 200 mg of titanium dioxide nanoparticles were dispersed in water at pH 5 and magnetically stirred for 1 hour at room temperature to obtain a titanium dioxide dispersion.
[0073] Mix 30 mL of water and 60 mL of ethanol thoroughly to prepare an ethanol-water mixed solution; disperse 9 mg of GO in the ethanol-water mixed solution to obtain a GO dispersion;
[0074] After mixing the GO dispersion and the titanium dioxide dispersion, the mixture was sonicated for 2 hours, then the solvent was removed, and the resulting composite material was calcined in a muffle furnace at 300°C for 3 hours to obtain the TiO2 / GO composite material.
[0075] (2) Preparation of TiO2 / GO@PLL bone-inducing composite material
[0076] The TiO2 / GO composite material was immersed in a PLL solution with a concentration of 0.8 g / L for 60 min. After filtration, it was dried in a normal drying oven at 60 °C for 2 h until completely dried, thus obtaining the TiO2 / GO@PLL bone-inducing composite material.
[0077] Comparative Example 1
[0078] A method for preparing a TiO2 / GO composite material includes the following steps:
[0079] 200 mg of titanium dioxide nanoparticles were dispersed in water at pH 4 and magnetically stirred for 1 hour at room temperature to obtain a titanium dioxide dispersion.
[0080] Mix 30 mL of water and 60 mL of ethanol thoroughly to prepare an ethanol-water mixed solution; disperse 10 mg of GO in the ethanol-water mixed solution to obtain a GO dispersion;
[0081] After mixing the GO dispersion and the titanium dioxide dispersion, the mixture was sonicated for 2 hours, then the solvent was removed, and the resulting composite material was calcined in a muffle furnace at 350°C for 2 hours to obtain the TiO2 / GO composite material.
[0082] The TiO2 / GO@PLL bone-inducing composites prepared in Examples 1-3 have equivalent properties. Therefore, only the TiO2 / GO@PLL bone-inducing composite prepared in Example 1 was used for performance testing. The specific tests are as follows.
[0083] Test 1: SEM Test
[0084] The TiO2 / GO@PLL bone-inducing composite material prepared in Example 1 was analyzed by SEM, and the results are as follows: Figure 1 As shown. Figure 1 The image shows the SEM images of the TiO2 / GO@PLL bone-inducing composite material and TiO2 prepared in Example 1 of this invention.
[0085] Depend on Figure 1 It can be seen that the TiO2 nanoparticles on the surface of the TiO2 / GO@PLL bone-inducing composite material are uniform in size and spherically distributed. This indicates that the electrostatic modification of GO facilitates the dispersion of the TiO2 nanoparticles. In this embodiment of the invention, graphene oxide is electrostatically modified onto the surface of titanium dioxide, and then amide bonds are formed through the free combination of the carboxyl groups of graphene oxide and the amino groups of lysine. This verifies that Example 1 of the present invention successfully synthesized the TiO2 / GO@PLL bone-inducing composite material.
[0086] Test 2: Antibacterial Performance Test
[0087] The antibacterial properties of the TiO2 / GO@PLL bone-inducing composite material prepared in Example 1, the TiO2 / GO composite material prepared in Comparative Example 1, and the raw material TiO2 were tested.
[0088] Test method: *Escherichia coli* and *Staphylococcus aureus* were used as bacterial strains. Under unirradiated conditions, the bacteria were cultured for 24 hours at 37℃. Under irradiated conditions, the bacteria were first irradiated with near-infrared light for 10 minutes at a power of 1.5 W·cm². -2 Bacterial culture for 3 hours; results are shown below. Figure 2 As shown. Figure 2 This is a graph showing the antibacterial data of the TiO2 / GO@PLL bone-inducing composite material prepared in Example 1 of the present invention.
[0089] Depend on Figure 2 The results showed that after 24 hours of incubation on the material surface, the bactericidal ability of pure TiO2 was weak, and the bacteria on the surface had vigorous metabolism, forming accumulated Escherichia coli and Staphylococcus aureus colonies.
[0090] Compared with TiO2, the number of Escherichia coli and Staphylococcus aureus colonies was significantly reduced in the TiO2 / GO composite material of Comparative Example 1 and the TiO2 / GO@PLL bone-inducing composite material of Example 1. This is because TiO2 and GO are electron-bound and have certain antibacterial properties.
[0091] Quantitative analysis results showed that TiO2 / GO@PLL had strong photothermal antibacterial ability against E. coli and S. aureus, and the antibacterial rates against Staphylococcus aureus and Escherichia coli were 100% and 100%, respectively.
[0092] In summary, the results demonstrate that the TiO2 / GO@PLL osteoinductive composite material prepared in this invention possesses unique properties due to non-covalent interactions, resulting in both inorganic and organic structures. This invention utilizes graphene oxide to electrostatically modify the surface of titanium dioxide to prepare the TiO2 / GO composite material. Then, through the free combination of the carboxyl groups of graphene oxide and the amino groups of lysine, amide bonds are formed, exhibiting strong adhesive forces that promote cell proliferation and adhesion, further enhancing the osteoinductive ability of the photoresponsive material. This constructs a potent bactericidal TiO2 / GO@PLL osteoinductive composite material with dual photoresponsiveness, possessing excellent biomimetic properties of natural hard tissue. It is expected to provide a basis for the preparation of novel, potent, antibacterial, and osteogenic biomedical materials with excellent comprehensive properties in both inorganic and organic forms.
[0093] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a TiO2 / GO@PLL bone-inducing composite material, characterized in that, Includes the following steps: Titanium dioxide dispersion and GO dispersion were ultrasonically mixed, and after removing the solvent, they were calcined at 300℃~350℃ to obtain TiO2 / GO composite material. The TiO2 / GO composite material was immersed in a polylysine solution to modify the surface of the TiO2 / GO composite material with polylysine, thus obtaining the TiO2 / GO@PLL bone-inducing composite material. The mass ratio of titanium dioxide to GO is 200:8-10; the concentration of polylysine solution is 0.8 g / L-1 g / L; the pH of titanium dioxide dispersion is 3-5; and the soaking time is 20 min-60 min.
2. The method for preparing the TiO2 / GO@PLL bone-inducing composite material according to claim 1, characterized in that, The titanium dioxide dispersion was prepared as follows: Titanium dioxide nanoparticles were dispersed in water at a pH of 3–5 to obtain a titanium dioxide dispersion.
3. The method for preparing the TiO2 / GO@PLL bone-inducing composite material according to claim 1, characterized in that, The GO dispersion was prepared as follows: GO was dispersed in an ethanol solution to obtain a GO dispersion.
4. The method for preparing the TiO2 / GO@PLL bone-inducing composite material according to claim 3, characterized in that, The volume percentage of the ethanol solution is 60-90%.
5. The method for preparing the TiO2 / GO@PLL bone-inducing composite material according to claim 1, characterized in that, The calcination time is 1 to 3 hours.
6. A TiO2 / GO@PLL bone-inducing composite material, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Bacterial cellulose based composite material having photocatalytic antibacterial property
CN105295105A
Titanium implant material with anti-infection and osseointegration promoting functions, and preparation method thereof
CN111035803A